Re-creating home: British colonialism, culture and the Zuurveld environment in the nineteenth century - Payne, Jill (Rhodes University, Faculty of Humanities, Department of History, 1999)
This thesis centres on the environmental impact of British colonialism in the Zuurveld during the nineteenth century. Within this context, it addresses the extent to which human-engineered environmental change is dictated by cultural mindset. Consideration of the links between culture and landscape transformation illuminates a little-considered aspect of the colonial experience in the Zuurveld. The British worldview at the turn of the eighteenth century is examined, with special reference to attitudes towards the environment. The changes which occurred in this attitude while the colonists adjusted to a foreign environment are traced. Precolonial societies manipulated the environment to a certain extent, but it was the British colonists who were to have the most profound effect on the ecosystem. The colonists impacted on the Zuurveld in a variety of ways. Much of the environmental change they induced resulted from their attempts to construct a familiar world from the alien landscape surrounding them. Attempts to "re-create home" in the Zuurveld were closely linked to the desire to exert control over what was to the colonists an "untamed wilderness." To this end land was cleared and new land use methods put into practice. Wildlife species threatening productivity were eliminated or forced through loss of habitat to retreat to the peripheries of the settlement. Exotic flora and fauna took the place of indigenes. The introduction of a capitalist economy meant that greater demands were made on the carrying capacity of the land. Conservation legislation introduced to limit increasing environmental degradation and protect commercial productivity simultaneously limited African access to the environment. Control of the land was closely linked to control of Africans: their labour was needed to facilitate the subjugation of the environment. Only through an appreciation of the British colonial mentality can changes to the Zuurveld environment during the nineteenth century be fully understood. Consequently, this study indicates that cultural mindset can play a pivotal role in shaping the environment.
Keywords: Imperialism -- Social aspects; Imperialism -- Environmental aspects -- South Africa; Imperialism -- Environmental aspects -- South Africa -- Eastern Cape